Formation of benzyl viologen-containing films at copper and their protective properties. (10th May 2020) - Carragher, Ursula; Breslin, Carmel B.
Abstract: Benzyl viologen (BV) was deposited at copper in the presence of chloride anions to generate a benzyl viologen-chloride layer at copper, where the viologen was present as a dication, stabilised by the negatively charged chloride anions. This layer provided good protective properties to the underlying copper substrate. On polarising the BV-modified copper in 0.1 M NaCl significantly lower currents, typically 28 μA cm −2, were observed at 0.40 V vs SCE compared to the higher currents of 1.75 mA cm −2 evident with the unmodified copper. The charge-transfer resistance at −0.15 V vs SCE, obtained from impedance data recorded in 0.1 M NaCl after 60 min, was measured as 21 kΩ cm 2 for copper indicating the build-up of corrosion products, while a lower resistance of 8 kΩ cm 2 was seen with the BV-modified copper. The estimated chloride content at the copper surface following immersion in chloride solutions was reduced from about 22% to 4% on modification with BV. Less protective properties were observed when the benzyl viologen was deposited from oxalate, sulfate and acetate solutions, and when the benzyl viologen was replaced with methyl or ethyl viologens, illustrating the importance of the supporting anions and viologen compound. The reduction of the di-cationic BV 2+ to the radical cation was observed at −0.57 V vs SCE, while the further reduction of the radical species was seen at −0.73 V vs SCE, indicating that the deposited benzyl viologen exhibits its characteristic redox properties.